1999
DOI: 10.1149/1.1392548
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Iron in Silicon Dioxide

Abstract: A quantitative analysis of diffusion of iron in silicon dioxide is presented. A source of iron deposited on the surface of thermally oxidized silicon wafers was diffused at temperatures ranging from 700-1100ЊC in an inert (nitrogen) ambient. The iron concentration in SiO 2 and Si was measured using total reflection X-ray fluorescence, deep level transient spectroscopy, and surface photovoltage techniques. A two-boundary diffusion model was applied to the experimental data to determine the diffusivity and segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
5
38
0
Order By: Relevance
“…They found that in bonded SOI wafers the diffusivity of iron was 2 ϫ 10 Ϫ14 cm 2 /s at 1050°C, and 10 Ϫ15 cm 2 /s at 900°C. These values are close to Fe diffusivity in silica glass measured by Atkinson et al, 27 and to the values of Ramappa et al, 28 who reported the equation D ϭ 4 ϫ 10 Ϫ8 exp(Ϫ1.51/kT). For comparison, the diffusivity of iron in crystalline silicon is in the range of 10 Ϫ6 cm 2 /s at the same temperatures.…”
Section: Modeling Resultssupporting
confidence: 90%
“…They found that in bonded SOI wafers the diffusivity of iron was 2 ϫ 10 Ϫ14 cm 2 /s at 1050°C, and 10 Ϫ15 cm 2 /s at 900°C. These values are close to Fe diffusivity in silica glass measured by Atkinson et al, 27 and to the values of Ramappa et al, 28 who reported the equation D ϭ 4 ϫ 10 Ϫ8 exp(Ϫ1.51/kT). For comparison, the diffusivity of iron in crystalline silicon is in the range of 10 Ϫ6 cm 2 /s at the same temperatures.…”
Section: Modeling Resultssupporting
confidence: 90%
“…This is because previous experimental data indicated that the diffusion of metallic atoms in SiO 2 and SiN x follows Fick's law of [17][18][19] The Gaussian distribution of the chemical composition at the interface in our unannealed samples should be attributed to the roughness at the HfO 2 / SiO 2 ͑SiON͒ interfaces and Hf diffusion that occurred during sample fabrication, such as during the Hf deposition. 12 Because the shape of the electron probe also affects the measured chemical distribution, the distribution is a convolution of the electron probe shape and the chemical distribution profile due to the roughness and the Hf diffusion at the interface.…”
Section: Discussionmentioning
confidence: 60%
“…This agrees with the work by Smith et al, 44 where the solubilities of iron in Si and SiO 2 were found to be similar. However, Ramappa and Henley 45 reported a strong tendency of iron to segregate into the SiO 2 layer. As discussed by Istratov et al in a review paper of iron in silicon, 1 the interaction of iron with SiO 2 and Si is complex and may involve chemical binding reactions that are dependent on the specific process conditions.…”
Section: Discussionmentioning
confidence: 99%